2020
DOI: 10.1371/journal.pone.0230464
|View full text |Cite
|
Sign up to set email alerts
|

Green fabricated zinc oxide nanoformulated media enhanced callus induction and regeneration dynamics of Panicum virgatum L.

Abstract: The current study focuses on the usage of bio synthesized zinc oxide nanoparticles to increase the tissue culture efficiency of important forage grass Panicum virgatum. Zinc being a micronutrient enhanced the callogenesis and regeneration efficiency of Panicum virgatum at different concentrations. Here, we synthesized zinc oxide nanoparticles through Cymbopogon citratus leaves extract to evaluate the effect of zinc oxide nanoparticles on plant regeneration ability in switchgrass. X-ray diffraction (XRD) and at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…These are shown in Figure 5b and in ZnO NPs, Zn and O are present in a higher density when compared to C. The elemental analysis of the prepared ZnO NPs was carried out by the energy-dispersive X-ray spectroscopy attached with the SEM (Figure 5c). The composition of each element contained in the as-prepared material is obtained from the EDX, which gives strong peaks of 57.2% for Zinc at 1.0, 8.6 and 9.5 eV and 26.2% for oxygen at 0.5 eV (Figure 5b), which are in good agreement with the previously reported work on the synthesis of ZnO NPs [82][83][84]. The presence of the carbon peak could be because of some carbon deposition during the calcination of the ZnO sample.…”
Section: Morphology Of Zno Npssupporting
confidence: 89%
“…These are shown in Figure 5b and in ZnO NPs, Zn and O are present in a higher density when compared to C. The elemental analysis of the prepared ZnO NPs was carried out by the energy-dispersive X-ray spectroscopy attached with the SEM (Figure 5c). The composition of each element contained in the as-prepared material is obtained from the EDX, which gives strong peaks of 57.2% for Zinc at 1.0, 8.6 and 9.5 eV and 26.2% for oxygen at 0.5 eV (Figure 5b), which are in good agreement with the previously reported work on the synthesis of ZnO NPs [82][83][84]. The presence of the carbon peak could be because of some carbon deposition during the calcination of the ZnO sample.…”
Section: Morphology Of Zno Npssupporting
confidence: 89%
“…Since they employed 3T3 fibroblasts from Balb mice, which are important connective tissue cells that aid in tissue repair and regeneration, and because these zinc oxide nanoparticles are benign to the cells, they can be used close to connective tissue cells. Shafique et al [ 153 ] reported that biosynthesized zinc oxide nanoparticles from a Cymbopogon citratus leaf extract were found, showing a promising callogenesis and regeneration frequency at their optimum concentrations (20 mg·L −1 and 30 mg·L −1 in the internodes and seeds, respectively) in Panicum virgatum , and it was confidently believed that this finding would open new doors in tissue culture technology by increasing the frequency of plant in vitro regeneration in different plant groupings.…”
Section: Biomedical Applications Of Plant-mediated Zinc Oxide Nanoparticlesmentioning
confidence: 99%
“…The implementation of this work is related to our development -an ointment composition -which is a combined agent with antimicrobial properties (due to the content of nanosilver) and regenerative properties (due to the content of highly dispersed Zinc oxide). Zinc oxide, being a source of the essential trace element Zinc, locally affects the skin area, releasing Zinc ions that saturate damaged tissues and promote accelerated regeneration of damaged skin [11,[22][23][24][25][26][27][28][29]. The ointment composition well moisturizes the damaged skin with the simultaneous restoration of the epidermis.…”
Section: Introductionmentioning
confidence: 99%